Ankle-Brachial Index predicts Coronary Artery Disease associated with Peripheral Arterial Disease (University Heart Journal, 2011)
Most common cause of Peripheral Arterial Disease (PAD) is atherosclerosis. Atherosclerosis is a generalized disease, also involving coronary and carotid arteries. Often atherosclerotic coronary artery disease (CAD) is associated with PAD. This prospective observational study was conducted in the National Institute of Cardiovascular Diseases, Dhaka, Bangladesh, during July 2004 to June 2005. Total 58 patients with PAD were included in the study. Patients were classified as group I having normal coronary artery, group II insignificant CAD (Left main